2003
DOI: 10.1177/0907568203010002006
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Children's Involvement in Decision-Making after Parental Separation

Abstract: This article argues that the assumption that it is a burden of responsibility for children to be involved in family or legal decision-making is problematic. Each child and family situation is unique, and children's perspectives provide valuable information on this. Children can communicate their views, intentions and difficulties provided that their social contexts and adult partners are sensitive to their perspectives. Within this context, the assumption that children lack sufficient age and maturity to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 9 publications
(6 reference statements)
4
66
0
7
Order By: Relevance
“…Smith et al (2003) interviewed 73 families with 103 children aged 7-18 years in New Zealand. When children were asked what advice they would give to separating parents, the most common response was ''let children have their say,'' ''listen to children,'' and ''tell children what is going on.'…”
Section: Families' Views On Their Participation In Legal Proceedingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith et al (2003) interviewed 73 families with 103 children aged 7-18 years in New Zealand. When children were asked what advice they would give to separating parents, the most common response was ''let children have their say,'' ''listen to children,'' and ''tell children what is going on.'…”
Section: Families' Views On Their Participation In Legal Proceedingsmentioning
confidence: 99%
“…However, there is now a sizable body of research and an emerging consensus in the field on general principles of interviewing children when legal decisions are pending, coalescing around a group of evidence-based interview techniques to either employ or avoid in concert with a more objective and neutral overall approach (Ceci, Crossman, Scullin, Gilstrap & Hufman, 2002;Cronch, Viljoen, & Hansen, 2006;Crossman, Powell, Pincipe, & Ceci, 2002;Lamb, Sternberg, Orbach, Esplin, Stewart, & Mitchell, 2003;London, 2001;Poole & Lamb, 1998;Saywitz & Camparo, 2009;Saywitz, Lyon, & Goodman, in press;Sternberg, Lamb, Davies, & Westcott, 2001;Wakefield, 2006;. Additionally, there are a number of studies that suggest children want to participate in the decision-making process and can provide both accurate and meaningful information, although they do not want to be responsible for the outcome of the case (Cashmore & Parkinson, 2008;Goodman & Melinder, 2007;Smith, Taylor & Tapp, 2003).…”
mentioning
confidence: 99%
“…In studies from New Zealand, only 2% of children wanted less contact with their father, particularly when the father was tough, angry or not interested [71,72]. Among college students who have experienced their parents' divorce 11 years earlier, more than half said they wanted to spend more time with their fathers.…”
Section: The Children's Conception About Living Arrangementsmentioning
confidence: 99%
“…Involvement of the child's voice, was in part, guided by research from two sources. First, research about children's competencies and rights revealed children's desire to be included in the process (Campbell, 2004;Graham & Fitzgerald, 2010a;James & Prout, 1997;Mayall, 1994;McIntosh, 2003;McIntosh, Well & Long, 2007;Parkinson & Cash-more, 2008;Smart, Neale & Wade, 2001;Smith, Taylor, & Tapp, 2003;United Nations, 1989). Second, researchers found that children and adults who participated in a process that involved children, thought it was potentially beneficial to them (Fitzgerald & Graham, 2011a;Goldson, 2006;Lodge & Alexander, 2010;McIntosh, 2000McIntosh, , 2003McIntosh, Wells, Smyth, & Long, 2008;Moloney & McIntosh, 2004).…”
Section: Introductionmentioning
confidence: 99%